Experimental Study on the Vertical Bearing Characteristic Model of Pile Groups in Complex Interactive Karst Pile Foundations - Xinquan Wang; Yongle Tian; Haibo Hu; Chen Liu; Haitao Chen; Jun Hong (Buildings)
In order to study the bearing characteristics of pile groups under the coupling of multiple caves, the influence of the interaction between the crossing cave, the underlying inclined cave, the pile-side cave, and the underlying cave on the ultimate bearing capacity, axial force, lateral friction, and load sharing ratio of the pile group was analyzed based on the model test. The research results show the following: (1) Due to the existence of the underlying cave, the Q-S curves of the pile groups are all steep drop types, and they show the characteristics of end-bearing piles. The influence of other caves is not obvious; the existence of beaded caves, lower crossing caves, underlying inclined caves, upper crossing caves, and pile-side caves will reduce the ultimate bearing capacity of the pile group. The reduction in the ultimate bearing capacity is 7.38%, 4.94% for the lower crossing cave, 2.59% for the underlying inclined cave, 2.27% for the upper crossing cave, and 0.74% for the pile-side cave. (2) When the pile body passes through the cave, the axial force changes slightly in the overburden layer, changes greatly in the limestone layer, and remains unchanged in the cave; under the same load level, the axial force of the pile close to the underlying inclined cave and the pile-side cave is smaller than that of the pile farther away. (3) Under the same load level, the lateral friction of the pile foundation shows a decreasing trend in the sand layer and limestone layer. The friction inside the sand layer is small. After entering the lime layer, the lateral friction increases sharply. The lateral friction is approximately 0 within the cave range. After passing through the cave, the lateral friction increases sharply. (4) The underlying inclined cave and the pile-side cave do not affect the position of the peak point of the pile foundation. The existence of the cave makes the pile foundation increase the peak point at the exit of the cave; under the same load level, the lateral friction of the pile close to the underlying inclined cave and the pile-side cave is larger than that of the pile farther away. (5) The existence of beaded caves, lower crossing caves, underlying inclined caves, upper crossing caves, and pile-side caves will increase the proportion of pile end resistance by 6.95%, 4.23%, 0.94%, 0.77%, and 0.62%, respectively. (6) This study systematically analyzed the differences in the degree of influence of different types of caves (including crossing caves, underlying inclined caves, and pile-side caves) on the bearing characteristics of pile foundations under the condition of the existence of underlying caves. It was found that beaded caves > lower crossing caves > underlying inclined caves > upper crossing caves > pile-side caves, which provides a priority decision-making basis for the optimal design of cave treatment schemes in engineering practice.